Perception of investors towards creating shareholders value - KUMAR, DR. P. PRAVEEN; MS. S. PADMAVATHI, (The journal of contemporary issues in business and government, 2020)
Investing in the stock market has its own benefits. Investing in the stock market will primarily help to grow money, by earning more profit from the invested amount. Taking high risk, by investing in risky investment avenues like in the stock market, would eventually help to increase or grow money. As taxes and inflation of a country have a major impact on wealth, investing in equities would protect and slow the negative impact on both. By regular payment of dividends to shareholders, regular investment income would be maintained by the investors which would help to meet their financial goals. Stock market has wide choices of financial instruments for investing like bonds, shares, derivatives, etc., which would benefit an investor to reduce the risk level by diversifying. Irrespective of shares owned by the investors, a portion of ownership is acquired and would benefit in voting rights and advice in strategic decisions made by the company. An analytical study is conducted on shareholder value creation with a sample of 87, through which different types of investors have delivered their perception on value creation. Different statistical tools are applied to identify their perception.